(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
A novel, simple, optimized reversed-phase chromatography method for assay of Tofisopam in pure and tablet form is developed. The experimental trial was by Box Behnken design using the Design Expert® software 10 version. The attributes selected were peak symmetry, number of theoretical, and peak purity. The predicted data satisfied with actual experimental data. The optimized chromatographic conditions required a quaternary pump with a mobile phase of Water: Acetonitrile 25:75 v/v at 1 mL/min, oven temperature at 25oC at 310 nm using C18(250 × 4.6 mm Id, 5μm) column and PDA detector with a run time of 5 min. The method was validated for linearity, precision, accuracy, and specificity. The method produced a linear response over a concentration range of 4–24 ppm with an overall average accuracy of 99.98%. The method was robust, reproducible, and specific with respect to the retention time of tofisopam.